The impact of divorce on return-Mmgration of family migrants - Govert Ewout Bijwaard; Stijn van Doeselaar (Institute for the Study of Labor (IZA), 2012)
Many migrants have non-labour motives to migrate and they differ substantially in their migration behaviour. Family migrants main migration motive is to join their future spouse. Thus, when their relation breaks down this influences their return decision. Using administrative panel data on the entire population of recent family immigrants to The Netherlands, we estimate the effect of a divorce on the hazard of leaving The Netherlands using the timing-of-events model. The model allows for correlated unobserved heterogeneity across the migration and the divorce processes. The family migrants are divided into three groups based on the Human Development Index (HDI) of their country of birth. We find that divorce has a large impact on the return of family migrants from less developed countries and less on the return of family migrants from developed countries. Young migrants with low income are influenced most by a divorce. We find some evidence of marriage for convenience for migrants from less developed countries. The impacts are quantified by graphing the impact of the timing of divorce on the return probability.
Keywords: J12; F22; C41; 330; temporary migration; timing of events method; marital status dynamics; Migranten; Familie; Scheidung; Rückwanderung; Niederlande